Detection vapour of nitrate fertiliser based explosives on transportation of nitrates during shipping using diphenylamine-calorimeter optic device - Noor Hazfalinda Hamzah; Mohd Faizal Abdul Rahman; Gina Francesca Gabriel; Khairul Osman (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study examines the ability of a Diphenylamine-Calorimeter Optical Device (DCOD) to detect the presence of nitrate in shipping containers. Fifteen selected inorganic fertilisers that potentially can be turned into an Improvised Explosive Device (IED) were analysed using UPLC-PDA. Results showed that only ammonium nitrate is suitable for turning into an IED and causing an explosion. A container model placed onboard a Malaysian Maritime vessel was used to determine the temperature and humidity experienced by nitrate during the voyage and at port. During the sea voyage (wet conditions), temperature and humidity were between 25-40.5 °C and 51.5-93.0%, respectively. In ports (dry conditions), the temperature ranged from 26.5-38.5 °C and 46-91% humidity. Using conventional tests in wet conditions, nitrous oxide was detectable with low reproducibility between 48-50 °C and vapour exposure duration of 850.0 to 895.0 s. While in dry conditions, nitrate oxide was detected regularly between 722.0 and 731.0 s and temperature between 44-50 °C. The sensitivity of the conventional and DCOD methods were evaluated and found to be similar. Field tests on DCOD were then conducted on nitrate stored in a container for 30 min, 1 h, 3 h and 2 days. Reading for positive results obtained were 67, 67, 11 and 0%, correspondingly. We conclude that DCOD can detect nitrate vapour in containers, but further modifications are required to increase its sensitivity.